Adsorption separation of heavy metals from simulated waste water using orange waste - Mohd Norawi, Mohd Azrul Hisyam (2006)
Orange waste it’s one of the resources to provide an adsorption gel for metal ion by simple chemical modification. Two types of adsorption gels, Ca2+-form and H+-form gels, were prepared by saponifying orange juice residues with calcium hydroxide and its subsequent acid treatment, respectively The Ca2+-form gel was effective for the complete and selective removal of is Pb(II), Cd(II), Zn(II), Mn(II)compared with other divalent metal ions. The selectivity order for metal ion uptake by the gel is Pb(II) > Cd(II) > Zn(II) > Mn(II).The experimental results clearly suggest that both gels are quite effective for removing heavy metal ions in acidic pH ranges.